PP113 High-Sensitivity C-Reactive Protein (hsCRP) Measurements And Burden In Patients With History Of Myocardial Infarction. (2017) - Deschaseaux, Celine; Agrawal, Rumjhum; Gabrielsen, Anders; Jindal, Ramandeep
Abstract : INTRODUCTION: The inflammatory marker C-reactive protein (CRP) can be measured by a high-sensitivity assay (hsCRP) specific to vascular inflammation. We aimed to identify published literature on prevalence of elevated hsCRP and associated clinical, economic, and humanistic burden in patients with a history of myocardial infarction (MI). METHODS: A comprehensive literature search was performed for publications in English between January 2000 and February 2016 in MEDLINE, EMBASE, and MEDLINE In-Process. Search terms were variations on 'Post myocardial infarction', 'CRP', 'epidemiology' and 'burden'. Clinical and real-world studies reporting baseline CRP levels in patients with a history of MI were included in the analysis. RESULTS: Ten studies (prevalence: two; burden: two; both: six) were included. Cut-off points in hsCRP assays varied from >2 mg/L to ≥5.9 mg/L. Prevalence of hsCRP levels >2, >2.3, ≥2.37 and ≥2.9 mg/L were reported in 36 percent, 49 percent, 50 percent and 33 percent of patients, respectively (one publication each). Two publications reported >3 mg/L levels in 27.6 percent and 53.7 percent of patients. Levels of ≥3.3, ≥3.8, ≥4.2 and ≥5.9 mg/L were found in 38.8 percent, 25 percent, 25 percent and 24.7 percent respectively (one publication each). Of six studies reported CV events, four studies found elevated hsCRP levels to be predictive of future risk. Elevated hsCRP levels independently predicted all-cause mortality in four studies and CV mortality in three studies. Three publications included data on comorbidities: Diabetes was associated with elevated hsCRP in two of three analyses; hypertension in one out of two. No consistent associations between elevated hsCRP levels and hyperlipidaemia (one study), stroke or angina pectoris (one study) were found. No study reported economic, resource use or quality-of-life burden. CONCLUSIONS: Due to limited evidence on prevalence of elevated hsCRP and associated burden of illness in patients with a history of MI, further research is warranted. Variations in findings, cut-off points and methods between studies make generalisations difficult.